Formation and diffusion of innovation in the court networks (Ius Novum, 2021)
The article presents the issue of diffusion of innovation in the court networks in Polandwith the use of the resources of knowledge of management. Attention is drawn to possiblethreats resulting from uncontrolled functioning of voluntary inter-organisational networks.The diagnosis was based on the source literature research method. It showed that first ofall close cooperation within the created inter-organisational networks can produce the besteconomic results for both organisations and their individual participants. However, it doesnot concern networks working within the justice system because they do not aim to achieveeconomic results but only to improve the mechanism of information and knowledge exchange.Nevertheless, the need to improve the quality of adjudication cannot take place without theimplementation of improvements facilitating it and the introduction of innovations in the fieldof management and diffusion of them in the court networks both horizontally and vertically.
Keywords: innovations; court networks; diffusion of innovation